Setting the agenda for further research on health and welfare. (13th November 2019) - Lhussier, M; Forster, N; Haighton, K; Egan, M; Woodhead, C; Webb, C; Poole, L; Carr, S M; Dalkin, S; Brown, H
Abstract: Background: Given the recognised relationship between poverty, welfare provision and health, welfare rights advice has emerged as a potentially key intervention in improving health and reducing inequalities. The generation of evidence in this area has proven difficult however, creating a need to take stock of existing research and develop an agenda for future work. Methods: A series of four workshops was convened involving researchers from four UK universities who had previously undertaken work examining the relationship between welfare advice and health, from a range of methodological perspectives. Run concurrently to a scoping of the literature, these workshops aimed to synthesise lessons from prior research; formulate outstanding research questions; and outline potential methodological approaches for addressing these. A survey was undertaken with professionals (from welfare or legal advice sectors, the health sector, commissioning, local government, and housing services, n = 50) to test out, refine and add to these research questions. Results: Key research questions developed from these workshops were: Are there inequalities in the impact and reach of advice services across social groups? How/ does advice delivery mode matter? What are the individual and system level impacts of the de-implementation of advice services? What are the impacts of changes to welfare provision on children, inter-generationally and throughout the life course? How do experiences of social welfare vary by social group, geographically and across generations? How do different identities combine to influence how social welfare is understood? Conclusions: While the collaborative process brought challenges in balancing research and practitioner expertise, this model of working has been successful in setting an agenda for further research with maximum utility to practice. Direct outputs from the projects have been the collaborative submission of a journal article and a research bid. Key messages: The collaboration, which was supported by the NIHR School of Public Health Research, led to the establishment of a concise research agenda. Through extensive stakeholder consultation, this will have maximal utility for practice.